Building Resilient Campuses: Harnessing Self-Efficacy to Tackle Human Resources Management Obstacles - Khuzaini, Khuzaini (JURNAL AL-TANZIM, 2024)
This study is based on the importance of effective human resource management in achieving the goals of higher education institutions, including producing quality graduates, improving academic reputation, and contributing to community development through self-efficacy. This study aims to analyze the role of self-efficacy in improving the performance and productivity of lecturers in higher education environments. This study uses a qualitative case study approach, with data collection techniques in the form of in-depth interviews, observation, and documentation. The findings show that lecturers and staff with high self-efficacy tend to be more confident in carrying out academic and administrative tasks, and are better able to adopt new technologies in the teaching and research process. These findings also indicate that high self-efficacy contributes to more appropriate and efficient decision making, reducing errors, and increasing the effectiveness of human resource management. The results of this study are expected to provide practical insights for higher education institutions to improve lecturer self-efficacy through appropriate training and management support, so that they can achieve better education, research, and service goals.